2018
DOI: 10.1159/000487438
|View full text |Cite
|
Sign up to set email alerts
|

A Risk-Adapted Approach to Patients with Stage I Seminoma according to the Status of Rete Testis: The Fourth Spanish Germ Cell Cancer Group Study

Abstract: Objective: The aim of this study was to assess a risk-adapted strategy for stage I seminoma guided by the presence of rete testis invasion. Methods: Between January 2013 and December 2015, a total of 135 consecutive patients with stage I seminoma from 18 Spanish tertiary hospitals were included in a prospective multicenter study. Median patient age was 38 years (range 22–60). Preoperative beta-human chorionic gonadotropin was elevated in 9.6% of patients. Rete testis invasion was present in 47.4% of patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The question arises whether the use of carboplatin is justified, having in mind modest benefit over AS in CSI seminoma patients. Similar conclusions could be drawn from several other studies, indicating that additional investigations are warranted to further evaluate the carbplatin role in the contemporary management of CSI [13,[72][73][74][75][76].…”
Section: Adjuvant Chemotherapysupporting
confidence: 84%
See 1 more Smart Citation
“…The question arises whether the use of carboplatin is justified, having in mind modest benefit over AS in CSI seminoma patients. Similar conclusions could be drawn from several other studies, indicating that additional investigations are warranted to further evaluate the carbplatin role in the contemporary management of CSI [13,[72][73][74][75][76].…”
Section: Adjuvant Chemotherapysupporting
confidence: 84%
“…In conclusion, 67% of patients did not receive adjuvant chemotherapy and majority of high-risk cases avoided disease recurrence. Apart from previous study, the fourth one by the Spanish Germ Cell Cancer Group maintained the same design and only included the existence of rete testis invasion as a predictive factor of a poorer outcome [75]. Invasion of rete testis was present in 47.4% of 135 CSI seminoma patients, and they received adjuvant carboplatin.…”
Section: Orchiectomy Tissue Specimensmentioning
confidence: 99%
“…Risk‐based management is proposed by some studies 18 , 19 , 20 , 21 and guidelines, 22 reserving adjuvant carboplatin for patients with one or both of rete testis involvement (RTI) or tumor size more than 4 cm. However, significant heterogeneity in the predictive value of these risk factors questions the reliability of this approach.…”
Section: Introductionmentioning
confidence: 99%
“…A risk-adapted approach seams feasible and showed that absence of both risk factors predicted an excellent outcome with a 3-year disease free survival of 94.9% [20].…”
mentioning
confidence: 99%